Exploring knowledge sharing intention of digitalization of rural intangible cultural heritage (DRICH): Integrating stimulus-organism-response (SOR) theory and social exchange theory (SET). - Bo Zhang; Yannan Zhang (PLoS ONE)
In the digital age, knowledge sharing is gaining increasing significance, but its contribution in promoting the protection and transmission of rural intangible cultural heritage is still not fully appreciated. Based on the stimulus-organism-response (SOR) theory and the social exchange theory (SET), this study developed a theoretical model to understand the knowledge sharing intention in the digitalization of rural intangible heritage (DRICH). We examined the influence of external stimuli (i.e., heritage rewards and heritage image) on organism feedback (i.e., cultural identity, responsibility, trust, and outcome expectation) and knowledge sharing intention. A total of 363 valid samples were obtained by means of questionnaire survey and analyzed by structural equation model. The results show that: (1) Heritage rewards and heritage image, as important external stimuli, have a positive impact on cultural identity; (2) Outcome expectation, trust and responsibility positively influence knowledge sharing intention, among which outcome expectation has the strongest effect; (3) Heritage-related self-efficacy (SE) positively moderates the relationship between cultural identity and responsibility. By exploring the influence mechanism of the sharing intention in DRICH, this study provides an empirical basis for the theory and practice of the protection and inheritance of rural intangible cultural heritage.